2022
DOI: 10.1002/bmc.5382
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a ultraperformance liquid chromatography–tandem mass spectrometry method for quantifying free and total dabigatran in human plasma: An application for a bioequivalence study

Abstract: Dabigatran etexilate mesylate (DABE), a prodrug, quickly changes into dabigatran (DAB) after its oral administration. Accordingly, detecting DABE in plasma is practically unmanageable. An ultraperformance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) technique was developed and validated to compute free DAB in participants. For the first time, the central composite design, a type of response surface methodology, was applied for optimizing variables affecting the cleavage of glucuronide bond. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The highly sensitive detection has been recently demonstrated by UHPLC/HPLC‐QqQ methods used for the bioequivalence study of dabigatran, which is the active metabolite of the prodrug dabigatran etexilate mesylate (Abd Allah et al, 2022), triamterene and hydrochlorothiazide (Margaryan et al, 2019), sumatriptan (Wichitnithad et al, 2020), and beraprost sodium (Prasaja et al, 2019). MS is also needed when the API does not contain chromophores for UV‐VIS detection, for example, bioequivalence study of isosorbide‐5‐mononitrate (Zhou et al, 2020) or the total amount of the drug in plasma and the unbound fractions are required, for example, bioequivalence study of paclitaxel protein‐bound particles for injectable suspension (Li et al, 2019).…”
Section: Ms‐based Methods In the Analysis Of Small‐molecule Chemical ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The highly sensitive detection has been recently demonstrated by UHPLC/HPLC‐QqQ methods used for the bioequivalence study of dabigatran, which is the active metabolite of the prodrug dabigatran etexilate mesylate (Abd Allah et al, 2022), triamterene and hydrochlorothiazide (Margaryan et al, 2019), sumatriptan (Wichitnithad et al, 2020), and beraprost sodium (Prasaja et al, 2019). MS is also needed when the API does not contain chromophores for UV‐VIS detection, for example, bioequivalence study of isosorbide‐5‐mononitrate (Zhou et al, 2020) or the total amount of the drug in plasma and the unbound fractions are required, for example, bioequivalence study of paclitaxel protein‐bound particles for injectable suspension (Li et al, 2019).…”
Section: Ms‐based Methods In the Analysis Of Small‐molecule Chemical ...mentioning
confidence: 99%
“…Bioequivalence studies must be demonstrated for the parent drug, and the determination of active metabolite is not recommended. The exceptions are prodrugs with very fast metabolization, for example, dabigatran etexilate mesylate (Abd Allah et al, 2022).…”
Section: Bioequivalence Studiesmentioning
confidence: 99%